Rossby Wave Breaking in Present and End-of-Century Climate - Lee, Ming Hon Franco (ETH Zurich, Department of Earth Sciences, Institute for Atmospheric and Climate Science, 2022)
Rossby waves are important drivers of the evolution of mid-latitude weather and their breaking (Rossby wave breaking, RWB) is known to initiate high-impact weather events such as heavy precipitation. Under global warming, the wave dynamics is expected to change and may possibly affect future extreme weather. In this study, the changes in RWB in a warming climate and their relationships to the jet (waveguide) and heavy precipitation are explored. Potential vorticity (PV) streamers and cutoffs are utilized as proxies for RWB events. Using a feature-based identification algorithm, their climatological frequencies are obtained in present-day and end-of-century climate model simulations of the Community Earth System Model (CESM). A comparison to ERA-Interim reanalysis demonstrates the ability of the CESM model to reproduce plausible seasonal cycles and geographical distributions of RWB despite an obvious isentropic level shift. The comparison between present-day and end-of-century climate simulations shows significant seasonal and regional changes of the climatological RWB frequencies. Prominent decreases in RWB frequency are observed near the North American west coast and the subtropical North Atlantic during boreal winter, while increases are seen in similar regions during boreal summer. These changes are mainly related to anticyclonic wave breaking (AWB) with the exception of the changes over the North American west coast in summer. Separated and merged jet configurations are revealed using composite zonal velocity fields during and outside of RWB occurrence. The changes in relative frequencies of the jet states are postulated to accompany the changes in RWB frequency. Though RWB is likely to remain as a trigger for heavy precipitation in future climate, the contribution from RWB changes in heavy precipitation redistribution cannot be quantified easily and other methods are required to explore this relationship.